A Network Technique for Analysis of the Thermal Transient Casting Process - Sulaiman, Shamsudin; Gathin, David T. (Universiti Putra Malaysia Press, 1996)
A network approach to simulating the thermal transient casting process is presented and compared with experimental data and a continuum finite element model. For a sufficiently fine network, all comparisons are good. The approach is economical on computer effort and may be used for a first iteration in die design. The capability to model successive casting cycles is presented, which shows the die thermal history to achieve stable operation